Airway inflammation, bronchial hyperresponsiveness, and anti-asthma therapy responses in cough variant asthma and classic asthma with FEV1% ≥80% predicted - Xue Zhang; Chengjian Lv; Huijuan Hao; Jingwang Lin; Min Zhang; Xue Tian (BMC Pulmonary Medicine)
Abstract Objective To explore the differentiation of airway inflammation, bronchial hyperresponsiveness and anti-asthma therapy responses between the cough variant asthma (CVA) and classic asthma (CA) patients with FEV1% ≥80% predicted. Methods In the first monocentre retrospective cross-sectional study, 402 patients with suspicion of CA and 544 patients with chronic cough were enrolled. Further prospective monocentre study was conducted and 66 patients of suspected asthma with negative bronchial dilation test (BDT) but positive bronchial challenge (BCT) test were enrolled and followed up for 4 weeks. Results CA patients had higher fractional exhaled nitric oxide (FENO) values than CVA patients (36.0 ppb vs. 24.0 ppb, p < 0.0001). The predictive value of FENO for positive BCT was significantly lower in chronic cough patients compared to those with suspicion of CA (AUC = 0.603 vs. 0.728). Following four weeks anti-asthma therapy, both the CVA and CA groups showed significant improvement in both the large and small airway function and symptom relief. There was no significant difference between the respective groups. The two most valuable spirometric variables for predicting a positive response to anti-asthma treatment were the improvements of FEV1 (ΔFEV1, cut-off values = 90 ml for CA and 110 ml for CVA) and FEV1% (ΔFEV1%, cut-off values = 3.49% for CA and 2.59% for CVA) after BDT in baseline of CA and CVA patients, respectively. Conclusion Patients with CVA exhibited lower levels of airway eosinophilic inflammation compared to those with mild CA. Most patients with mild CA and CVA could benefit promptly from anti-asthma treatment. Additionally, an improvement in FEV1 and FEV1% during BDT can potentially predict positive responses to anti-asthma therapy in both groups.